2022
DOI: 10.3389/fphys.2022.846620
|View full text |Cite
|
Sign up to set email alerts
|

Anti-atrial Fibrillation Effects of Pulmonary Vein Isolation With or Without Ablation Gaps: A Computational Modeling Study

Abstract: BackgroundAlthough pulmonary vein isolation (PVI) gaps contribute to recurrence after atrial fibrillation (AF) catheter ablation, the mechanism is unclear. We used realistic computational human AF modeling to explore the AF wave-dynamic changes of PVI with gaps (PVI-gaps).MethodsWe included 40 patients (80% male, 61.0 ± 9.8 years old, 92.5% persistent AF) who underwent AF catheter ablation to develop our realistic computational AF model. We compared the effects of a complete PVI (CPVI) and PVI-gap (2-mm × 4) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…that led to PVI ablation becoming the cornerstone of clinical therapy for AF, several computational models were developed to test the effectiveness of various PVI ablation strategies. 69 , 70 Using CT-based atrial models, Hwang et al. compared the outcome of different ablation strategies and concluded that the most effective one was PVI with posterior box isolation and anterior line ablation.…”
Section: Computational Models Of Af – Uniting Insights From Animal Mo...mentioning
confidence: 99%
“…that led to PVI ablation becoming the cornerstone of clinical therapy for AF, several computational models were developed to test the effectiveness of various PVI ablation strategies. 69 , 70 Using CT-based atrial models, Hwang et al. compared the outcome of different ablation strategies and concluded that the most effective one was PVI with posterior box isolation and anterior line ablation.…”
Section: Computational Models Of Af – Uniting Insights From Animal Mo...mentioning
confidence: 99%
“…AF digital twins can simulate the results of various virtual interventions under identical and reproducible conditions without posing ethical concerns 10 . Recently, we reported a digital twin study that could evaluate AF wave dynamics and rhythm outcomes by creating PVI gap models 11 . Therefore, we utilized a realistic human AF digital twin, incorporating the left atrial (LA) anatomy and electrophysiology of 50 AF cases.…”
Section: Introductionmentioning
confidence: 99%
“…With recent improvements in computational technology and power, sophisticated AF computation modeling has become possible. Virtual ablation or virtual AAD responses can be tested on a virtual twin that reflects the anatomy, fibrosis, fiber orientation, and electrophysiological characteristics of patients with AF, and the wave dynamics generated from hundreds of thousands of nodes can also be evaluated ( 15 18 ).…”
Section: Introductionmentioning
confidence: 99%